Algorithm for Optimizing Train Operation Modes Based on Timetable Parameters (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article focuses on developing an algorithm to optimize the switching points of train movement modes, taking into account scheduled time, movement resistance, gradients, and rolling stock characteristics. The primary emphasis is on modeling the movement process, calculating speed and time increments, and considering the impact of gradients on train movement. The developed mathematical model and algorithm aim to minimize deviations from the planned arrival time and optimize train movement modes. The methodology described in the article can be applied to enhance railway transportation efficiency, improve travel time calculation accuracy, and reduce energy consumption during train operation.